Malay Mail, 29 April 2004 - Pauline Almeida
The horrible death of two-year-old Norishzyani Amylia Ahmad, a child abuse victim from Damansara Damai, Sungai Buloh, Selangor, has left the non-governmental organisations angry and in shock.